Angiosarcoma of the Retroperitoneum: Report on a Patient Treated with Sunitinib. (11th May 2009) - Yoo, Changhoon; Kim, Jeong-Eun; Yoon, Shin-Kyo; Kim, Song Cheol; Ahn, Jin-Hee; Kim, Tae Won; Suh, Cheolwon; Lee, Jae-Lyun
Abstract : A 52 year-old woman presented with an incidentally detected retroperitoneal angiosarcoma and multiple hepatic metastases. After chemotherapy with weekly paclitaxel and doxorubicin, angiosarcoma had progressed rapidly. Because few chemotherapeutic options were available for her, sunitinib (37.5 mg/day, daily) as a salvage regimen was administered. Although sunitinib was interrupted after two weeks due to hematologic abnormalities, some metastatic nodules were regressed. Therefore, sunitinib was recommenced at a reduced dose (25 mg/day, daily). Serial computed tomography scans showed variable response in each tumor, however, sunitinib at least delayed tumor progression, compared to previous chemotherapy. With this case report, we suggest sunitinib may be effective against angiosarcomas. When sunitinib is administered to patients with angiosarcomas, hematologic abnormalities should be monitored frequently as severe hematologic toxicity may be caused either by sunitinib per se or angiosarcoma.